Observação do controle ambiental em um grupo de pacientes portadores de asma atendidos no ambulatório de pneumologia do Hospital Universitário João de Barros Barreto quanto ao uso de capas impermeáveis no colchão e travesseiro - SARRAF, Jaime Daniel Alves (2019)
Objective: To evaluate the clinical improvement of patients with moderate to severe persistent asthma, before and after the use of an impermeable cape of tactel on the bed and pillow. Methods: It consists of a pilot, observational and descriptive study, involving 15 patients from the pulmonology outpatient clinic of the University Hospital João de Barros Barreto, in the period between July and August 2017. Fifteen patients were donated an impermeable cape of tactel to cover the mattress and pillow. For the evaluation, questionnaires were applied to study the clinical symptoms of the disease, before and after the use of the cover. Results: Twelve patients returned to the second phase of the study. The mean age was 53 years, of which 11 were female. Eight patients had incomplete elementary education and none had a higher education level. The use of the cape decreased both the frequency and intensity of asthma symptoms in this group of patients. There was also a decrease in workrelated absences or impairment of normal activities and the number of asthma attacks. Conclusion: The use of the impermeable cape of tactel showed satisfactory results in the clinical improvement of the group of patients studied, showing to be an important aspect in the environmental control of patients with asthma.